Askese som social/politisk mobilisering: Joseph Alters bog om Gandhi, Gandhi’s Body - Aktor, Mikael (Religionsvidenskabeligt Tidsskrift, 2016)
There are several historical examples of asceticism as a means to social and political mobilization. Gandhi’s use of fasts and sexual abstinence in the larger fight for national independence is a well-known recent example. Joseph Alter’s book, Gandhi’s Body: Sex, Diet, and the Politics of Nationalism from 2000 is a relevant source for such considerations. Alter describes Gandhi’s personal experiments with public health, fast, food, sexual abstinence and both traditional and Western medicine in the perspective of national independence. For Gandhi ascetic practices were at the same time personal and for the sake of the nation. He saw his own success in these practices as guarantee of the necessary social and political changes. ‘Truth’ was the keyword in Gandhi’s thinking because he regarded truth as a transforming power. The non-violent resistance will either force injustice to yield or it will force it to reveal its true, violent face. But to activate truth one has to integrate truth in one’s own being. In this Gandhi was in line with an ascetic tradition that has been described by Peter Brown, Michel Foucault and Talal Asad: By eliminating the private I through awareness of hidden desires and through public confession the ascet-ic reaches a state of transparency where the veil between him-/herself and God/Truth is removed. This kind of socially and politically mobilizing asceticism indicates how the ascetic can be a component in a more collective social dynamics.